Still standing : the untold story of my fight against gossip, hate, and political attacks - Prejean, Carrie, 1987- (Washington, D.C. : Regnery Pub., 2009)
Carrie Prejean had no idea, when she walked down the stage to face her final question before the selection and crowning of Miss USA, that her hopes, dreams, and reputation were about to come crashing down around her under a torrent of media attacks. Her crime? To have answered honestly that for her--and for most Americans--marriage is defined as a sacred bond between one man and one woman. For the thought crime of saying this, Carrie Prejean went from being the likely winner of the Miss USA competition to being the certain loser. She would be subjected to a campaign of vilification, verbal abuse, and betrayal that did not even end with her being stripped of her title of Miss California. Here at last is Carrie's own story--the full story--about what actually happened.--From publisher description.
My moment of truth -- Standing up for myself -- Just another sport -- Planet Hollywood -- Meeting Perez -- Was it something I said? -- A wing and a prayer -- A warm bucket of pig blood -- Fired by radio -- Gagging free speech -- Stand for yourself.
Includes index.
Keywords: Prejean, Carrie, -- 1987-; Beauty contestants -- United States -- Biography; Models (Persons) -- United States -- Biography